A silicon carbide thermistor - Boltovets, N.S.; Kholevchuk, V.V.; Konakova, R.V.; Kudryk, Ya.Ya.; Lytvyn, P.M.; Milenin, V.V.; Mitin, V.F.; Mitin, E.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
We consider a silicon carbide thermistor with multilayer Au–TiBx–Ni2Si ohmic contacts intended for operation in the 77 to 450 K temperature range.